KASUS PENCEMARAN NAMA BAIK LUHUT BINSAR PANJAITAN BERDASARKAN PERSPEKTIF SEMIOTIKA LAGU “ANGGURMAN” - Hasan Fadli; Ratnaningrum Zusyana Dewi; Masnia Ningsih (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2024)
Freedom of speech is one of the most protected human rights. However, in the process it turned out that there were still violations of freedom of expression, especially during the New Order government. Many activists and artists were born who opposed the authoritarian attitude of the New Order through their works. After the fall of the New Order, the Reformation returned to Indonesia's right to freedom of speech. After several years, there have been threats regarding violations of the right to freedom of expression with the emergence of the "rubber" article in the 2008 ITE Law. One of the most recent cases regarding this article is the defamation of Luhut Binsar Panjaitan. Jason Ranti, an artist who is also an activist, is challenging this regulation through his work entitled "Anggurman". Therefore it is appropriate to do research on the defamation case of Luhut Binsar Panjaitan from the perspective of the semiotics of the song "Anggurman". The research method used in this journal is qualitative with analysis Michael Riffaterre's semiotic approach. The result of this research is that this song can really describe the case above because the storyline of this song is the same as this case of defamation.